2021
DOI: 10.3390/ijerph181910449
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Link between Balance and Body Mass Composition in Children and Adolescents?

Abstract: School-age children are particularly prone to disturbances in body composition, because this is a period of intensive growth and a period in which correct habits are shaped, especially in relation to diet. This is why it is so important to diagnose emerging disorders early so as to implement therapeutic or educational activities. The aim of this study was to assess the relationship between the factors of body mass composition and body mass index (BMI), as well as the balance parameters in children and adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
5
6
0
1
Order By: Relevance
“…This fact may also be related to the fact that older young people have more weight. The BMI results are consistent with studies that have found a negative correlation between balance and BMI [41] and also are in line with the results of a recent study in which children and adolescents with higher BMI performed better on balance parameters [33].…”
Section: Anthropometric Variables Static Balance and Posturesupporting
confidence: 92%
See 1 more Smart Citation
“…This fact may also be related to the fact that older young people have more weight. The BMI results are consistent with studies that have found a negative correlation between balance and BMI [41] and also are in line with the results of a recent study in which children and adolescents with higher BMI performed better on balance parameters [33].…”
Section: Anthropometric Variables Static Balance and Posturesupporting
confidence: 92%
“…This observation may indicate the higher stability of the girls. This finding is consistent with the studies conducted by Rusek et al [33] and Ludwig et al [15]. These observations have also been made in other studies in adults [34,35]; therefore, it will be important for future studies to examine more closely the neuromuscular patterns associated with gender differences.…”
Section: Differences Between Genderssupporting
confidence: 91%
“…The displacements of the center of gravity were recorded at a frequency of 100 Hz. The method assesses postural sway while a patient is standing in a fixed standing position (static test) based on graphical records of displacements of the point of application of the resultant forces of pressure with feet on the ground (COP—center of pressure) [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many authors have analyzed the body mass index and its impact on body balance, but the results of the authors’ research differ in terms of their results. Scientists evaluated the relationship between body mass index (BMI) factors and balance parameters in children and adolescents [ 24 ]. The study group consisted of 1337 children aged 7 to 15.…”
Section: Introductionmentioning
confidence: 99%